Development and Establishment of Mining Equipment Component Management Strategy: A Consideration form Cost-Benefit Point of View - Purwa, Anggra Wishnu; Adhiutama, Akbar (The Indonesian Journal of Business Administration, 2015)
Abstract. In a coal mining operation, maintenance of mining equipment holds significant roles that influence overall productivities. From cost point of view, maintenance of mining equipment has a serious impact as well to the cost of production. And, on behalf of maintenance activities, the availability of components and the reliability of component supply is strategic because without components there is no maintenance of mining equipment. The main purpose of this thesis is to scrutinize the strategy of maintenance of mining equipment components that satisfy demand from mining equipment maintenance activities. This thesis suggests comprehending the knowledge and skill of managing the aspects of component maintenance; that will help supplying mining equipment components for maintenance activities in most efficient and effective ways.Key Words:Material Managements, Rotable Spare Parts Management, Repairable Spare Parts Management, Inventory Policy